The Effectiveness of Methanol and Hexane Extracts of Clove Leaves on The Growth of The Fungus Sclerotium rolfsii which Causes Damping-off Disease in Soybean Plants (Glycine max L. Merr) - Parwanayoni, Ni Made Susun; Suryanti, Ida Ayu Putu; Permana, I Gede Teguh (Journal of Tropical Plant Protection, 2026)
Differences in the polarity of solvents used in extraction significantly affect the inhibitory power and types of compounds identified. The aim of this study was to determine the inhibitory effectiveness of clove leaf extract extracted with different solvents, namely methanol (polar) and hexane (non-polar), on the growth of Sclerotium rolfsii fungus. The research methods included: extraction of clove leaf extract with methanol and hexane solvents, and testing the inhibitory power of crude methanol and hexane extracts using the well diffusion method. The effectiveness of clove leaf extract on the growth of S.rolfsii fungal colonies was tested using the colony method and biomass test. The results showed that the inhibitory power of crude clove leaf extract, tested separately with methanol and hexane solvents, each with an inhibition zone diameter of 40 mm (very strong inhibition) and  0 mm (no inhibition). The results extract tests on the growth of S.rolfsii fungal colonies showed that a 2 % methanol extract concentration was able to inhibit 100 % of S.rolfsii fungal colony growth.The results of the activity test of clove leaf methanol extract on the growth of fungal biomass S.rolfsii showed 100 % inhibition at a concentration of  1.5 %. The clove leaf methanol extract showed very strong inhibition, while the hexane extract showed no inhibition against S.rolfsii fungal growth.